Preparation method of semiconductor composite device and semiconductor superconducting composite device thereof
Through micro-nano processing methods combined with electron beam exposure, plasma etching and thin film deposition technology, the problem of inflexible and universal production methods in the existing technology is solved, and the modification of the interface of semiconductor composite devices and the various types of devices are realized. High-quality production improves the versatility and applicability of the process.
Patent Information
- Application Number
- CN202310794749.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The existing composite device manufacturing methods are not flexible and universal enough, and cannot flexibly change the nature of the interface, limiting the diversity of device types and research applications.
The micro-nano processing method is adopted, combined with electron beam exposure, plasma etching and thin-film deposition technology, and the modification of the interface of semiconductor composite devices and the production of various types of devices by controlling the etching conditions and thin-film deposition steps.
It realizes high-quality production and flexible adjustment of interface properties of different types of composite devices, improves the versatility and applicability of the process, can produce complex devices and change interface properties, and is suitable for different research needs.
Smart Images

Figure CN119233746A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite device manufacturing, and in particular relates to a method for preparing a semiconductor composite device and a semiconductor superconducting composite device. Background Art
[0002] In the field of composite device research, the fabrication of composite devices is the foundation of everything. Composite devices composed of different materials exhibit a variety of interesting physical phenomena. Different device structures also exhibit different phenomena, which are used to study different properties and promote the progress of basic scientific research and device application research. For example, theory predicts that composite devices of strong spin-orbit coupling semiconductor nanowires and superconductors can enter the topological region under parallel magnetic fields, and Majorana zero energy touches appear at the endpoints, which are used for topological quantum computing. The preparation of composite devices is of great significance to basic scientific research and future applications.
[0003] The production of high-quality semiconductor superconducting composite devices currently includes the use of nanowires to shield the growth of superconducting films and the use of smart wall technology to process composite devices. Both methods can avoid the use of photoresists in device processing, thereby obtaining clean interfaces and high-quality composite devices. However, both methods have strong limitations and are inconvenient to use. The first is the method of shielding with nanowires or nanosheets. Using the nanowire shielding method, a single junction or two junctions can be made when growing superconducting films. If nanowire shielding is used, some nanowires can be left uncovered by superconducting films. This method is limited to devices with simple structures and requires finding suitable shielded nanowires in the substrate after growth. In a batch of devices, the properties of the interfaces are basically the same, and it is not easy to obtain devices with different interfaces. Another method is to use smart wall shielding, which uses artificially constructed insulating complex structures as shielding to form devices when evaporating superconducting films. Because the structure can be constructed using the general Wiener processing method, relatively complex devices can be made. However, each device requires a separate smart wall design and process optimization. This method is not very flexible, and a lot of work needs to be done to change the device type. Therefore, the present invention utilizes a relatively common micro-nano processing method to manufacture composite devices, and the process can be extended to different types of devices, a variety of different coating methods, and can process interfaces. Summary of the invention
[0004] Therefore, the purpose of the present invention is to overcome the defects in the prior art and provide a method for preparing a semiconductor composite device and a semiconductor superconducting composite device thereof, so as to solve the problems that the existing composite device manufacturing method is not flexible and universal enough and the interface properties cannot be flexibly changed during the process.
[0005] Before describing the present invention, the terms used in this article are defined as follows:
[0006] The term "PMMA" means: polymethyl methacrylate.
[0007] The term "Vbias" means: bias voltage.
[0008] The term "back gate" refers to a gate with an insulating substrate as the dielectric.
[0009] The term "MIBK" means: methyl isobutyl ketone.
[0010] The term "IPA" means: Isopropyl alcohol.
[0011] The term "xylene" means: xylene.
[0012] The term "p-dioxane" refers to: 1,4-dioxane.
[0013] The term "MIAK" means: methyl isoamyl ketone.
[0014] The term "2-pentanone" refers to: 2-pentanone.
[0015] The term "MEK" means: methyl ethyl ketone.
[0016] The term "ethanol" means: ethyl alcohol.
[0017] The term "TMAH" means: tetramethylammonium hydroxide.
[0018] The term "DI" means: deionized water.
[0019] The term "ZEP" means: styrene methacrylate.
[0020] The term "EBR-9" refers to: electron beam exposure ninth generation photoresist.
[0021] The term "HSQ" means: Hydrosilicates.
[0022] The term "COP" means: Epoxy Polymer
[0023] The term "PBS" refers to: polyisobutylene dioxide phosphate buffered saline.
[0024] To achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a semiconductor composite device, wherein the method prepares the semiconductor composite device by a micro-nano processing method, and performs interface modification by controlling the micro-nano processing step; wherein:
[0025] The micro-nano processing method is selected from one or more of the following: electron beam exposure, plasma etching, and thin film deposition;
[0026] Preferably, the thin film deposition method is selected from one or more of the following: electron beam evaporation, magnetron sputtering, and resistance thermal evaporation.
[0027] According to the preparation method of the first aspect of the present invention, the preparation method comprises the following steps:
[0028] (1) Design exposure patterns for semiconductor composite devices;
[0029] (2) exposing and developing based on step (1);
[0030] (3) etching the interface of the semiconductor material based on step (2);
[0031] (4) depositing a thin film based on step (3);
[0032] (5) removing the glue and peeling off the excess film to obtain the semiconductor composite device;
[0033] Preferably, the interface modification is performed by controlling the etching conditions in step (3).
[0034] According to the preparation method of the first aspect of the present invention, the step (1) further comprises: spin coating a photoresist on a substrate carrying the semiconductor material and baking the photoresist before designing the exposure pattern of the semiconductor material;
[0035] Preferably, the baking time is 1 to 15 minutes, more preferably 1 to 5 minutes, and further preferably 1 to 3 minutes;
[0036] Preferably, the photoresist is selected from one or more of the following: PMMA, ZEP, EBR-9, HSQ, PBS, COP, more preferably selected from one or more of the following: PMMA, ZEP, EBR-9, PBS, further preferably: PMMA or ZEP; and / or
[0037] Preferably, the substrate is selected from one or more of the following: SiO2, Si3N4, intrinsic silicon, sapphire, GaN, mica sheet, quartz glass, more preferably selected from one or more of the following: SiO2, Si3N4, intrinsic silicon, sapphire, GaN, further preferably selected from one or more of the following: SiO2, intrinsic silicon, sapphire.
[0038] According to the preparation method of the first aspect of the present invention, in the step (2), exposure and development are performed according to the pattern designed in the step (1) by an electron beam exposure system;
[0039] Preferably, the composite device structure is defined by the electron beam exposure system, and its structure width and position accuracy are both less than 100 nm, more preferably less than 90 nm, further preferably less than 70 nm, and further preferably less than 50 nm;
[0040] Preferably, the developer is selected from one or more of the following: MIBK:IPA mixed solution, xylene:p-dioxane mixed solution, MIAK:2-pentanone mixed solution, MEK:ethanol mixed solution, TMAH:DI mixed solution, more preferably selected from one or more of the following: MIBK / IPA mixed solution, xylene / p-dioxane mixed solution, MIAK / 2-pentanone mixed solution, further preferably: MIBK:IPA mixed solution or xylene:p-dioxane mixed solution;
[0041] Preferably, the development time is 30 to 600 s, more preferably 30 to 300 s, and further preferably 30 to 180 s; and / or
[0042] Preferably, the exposure time is 1 to 300 s, more preferably 1 to 180 s, and further preferably 1 to 60 s.
[0043] According to the preparation method of the first aspect of the present invention, in the step (3), the adsorbed atoms and the oxide layer on the surface of the semiconductor material are removed by a plasma etching system, and the interface properties are changed.
[0044] According to the preparation method of the first aspect of the present invention, in said step (3),
[0045] The etching time is 5 to 600 s, preferably 5 to 240 s, more preferably 5 to 120 s;
[0046] The etching gas is selected from one or more of the following: Ar, O2, CF4, SF6, NF3, SiCl4, CH4, H2, preferably selected from one or more of the following: Ar, O2, CF4, SF6, NF3, SiCl4, more preferably selected from one or more of the following: Ar, O2, CF4, SF6;
[0047] The etching gas pressure is ≤10Pa, preferably ≤8Pa, more preferably ≤5Pa;
[0048] The etching ion beam current is ≥10mA, preferably ≥15mA, more preferably ≥20mA; and / or
[0049] The etching ion beam voltage is ≤1000V, preferably ≤800V, and more preferably ≤600V.
[0050] According to the preparation method of the first aspect of the present invention, wherein, in the step (4), the film is transferred to the film deposition chamber by vacuum to avoid exposure to the atmosphere, which may cause surface adsorption or secondary oxidation of the interface; wherein the film is a metal film;
[0051] Preferably, the material of the film is selected from one or more of the following: aluminum, lead, niobium titanium nitride, tin, more preferably selected from one or more of the following: aluminum, lead, niobium titanium nitride, further preferably aluminum or lead; and / or
[0052] Preferably, the step (4) further comprises using a cold base plate to improve the quality of the deposited film.
[0053] According to the preparation method of the first aspect of the present invention, in the step (4), a transition layer is deposited to prevent direct oxidation of the interface, and then the film is transferred to a thin film deposition device for thin film deposition; wherein the thin film is a metal thin film;
[0054] Preferably, the material of the film is selected from one or more of the following: aluminum, lead, niobium titanium nitride, tin, more preferably selected from one or more of the following: aluminum, lead, niobium titanium nitride, further preferably aluminum or lead; and / or
[0055] Preferably, the step (4) further comprises using a cold base plate to improve the quality of the deposited film.
[0056] According to the preparation method of the first aspect of the present invention, in the step (5), the sample after the thin film deposition is placed in a degumming solution, and the excess thin film is peeled off to obtain the semiconductor composite device;
[0057] Preferably, the degumming solution is selected from one or more of the following: acetone, methyl isobutyl ketone, butyl acetate, dimethylformamide, dichloromethane, propylene glycol monomethyl ether acetate, trichloroethylene, N-methylpyrrolidone, methyl ethyl ketone, more preferably selected from one or more of the following: acetone, methyl isopropyl ketone, butyl acetate, dimethylformamide, propylene glycol monomethyl ether acetate, trichloroethylene, further preferably selected from one or more of the following: acetone, methyl isopropyl ketone, butyl acetate, dimethylformamide, propylene glycol monomethyl ether acetate; and / or
[0058] Preferably, the auxiliary method for degumming is selected from one or more of the following: blowing with a dropper, blowing with an air gun, and ultrasonic vibration.
[0059] A second aspect of the present invention provides a semiconductor superconducting composite device, wherein the semiconductor superconducting composite device is manufactured according to the manufacturing method described in the first aspect.
[0060] According to a specific embodiment of the present invention, the universal method for manufacturing high-quality semiconductor superconducting composite devices and adjusting interface properties of the present invention manufactures composite devices in a universal micro-nano processing manner, and the interface properties are adjusted by etching in one step. It includes the following steps:
[0061] (1) Defining the pattern of the composite device using an electron beam exposure system;
[0062] (2) Use etching to remove the oxide layer of semiconductor materials and modify the interface.
[0063] (3) Use thin film deposition technology to deposit the upper layer material to make a composite device.
[0064] (4) Use solvent to remove the glue and peel off the excess film to obtain the desired composite device.
[0065] Wherein, step (1) graph definition includes the following steps:
[0066] (1) Spin-coat photoresist onto a substrate carrying semiconductor material.
[0067] (2) Use the electronic book exposure system to expose the photoresist according to the required pattern.
[0068] (3) Develop the exposed substrate to obtain the desired pattern.
[0069] The method for preparing the etched surface in step (2) is to generate plasma using a certain pressure gas, apply voltage to guide the plasma to bombard the sample surface, remove the surface oxide layer and change the interface properties.
[0070] The thin film deposition preparation method described in step (3) is to use vacuum transmission to the thin film deposition chamber to avoid exposure to the atmosphere, which may cause surface adsorption or secondary oxidation of the interface. Alternatively, a transition layer is deposited to prevent direct oxidation of the interface. Then the thin film is transferred to the thin film deposition equipment for thin film deposition.
[0071] The solvent degumming method described in step (4) is to select degumming solvent according to different glues, and remove the excess film by blowing with a dropper, blowing with an air gun or ultrasonic vibration.
[0072] According to another specific embodiment of the present invention, the method of the present invention integrates a set of universal Wiener processing methods, utilizing an electron beam exposure system, a plasma etching system and a thin film deposition system, wherein the thin film deposition system includes but is not limited to an electron beam evaporation coating system and a magnetron sputtering coating system, and the coating system can be modified to add a cold bottom plate coating. The processing and interface property changes of different types of high-quality composite devices under similar process conditions are achieved. The electron beam exposure system can define the structure of the composite device with high precision, and the structural width and position accuracy can be less than 100nm. The plasma etching system can use different gases to generate plasma. Taking argon as an example, the plasma is electrically neutral as a whole, but the electrons in the Ar atoms are separated from the atoms, and the atoms present positive charges. Under the action of voltage, it can be accelerated and physically bombarded to etch the surface of the material to achieve the purpose of removing adsorbed atoms and oxide layers. The electron beam evaporation coating system uses electrons to bombard metal materials and heat them to melt. After the material evaporates, it is adsorbed to the bottom surface to form a thin film. In the magnetron sputtering coating system, negative voltage is applied to the target, inert gas is flushed into the cavity, and high voltage is used to accelerate electrons. Under the action of the magnetic field, the electrons perform cyclotron motion, increase the motion trajectory, collide with and charge argon atoms, generate plasma, and the atoms become positively charged. Under negative pressure acceleration, they bombard the target, and the sputtered target material clusters fall onto the substrate to form a thin film. These universal Wiener processing methods make the explored methods more widely applicable.
[0073] In order to solve the problem that the existing composite device manufacturing method is not flexible and universal enough and the interface properties cannot be flexibly changed during the process, the purpose of the present invention is to explore a set of methods for manufacturing high-quality composite devices based on the traditional general Wiener processing method and change the interface properties by etching. This set of micro-nano processing methods combines electron beam exposure, plasma etching and thin film deposition technology, and optimizes the process to achieve universal composite device manufacturing and interface property changes. Due to the versatility of the Wiener processing method, this method can manufacture different types of composite devices with fewer restrictions, and different film types, film thicknesses, etc. can be replaced, and low-temperature thin film evaporation can also be achieved. The processing of a variety of high-quality composite devices under similar process conditions has been achieved. It provides a basis for future research of different types using different devices.
[0074] The method for preparing and modifying the interface of the semiconductor composite device of the present invention may have, but is not limited to, the following beneficial effects:
[0075] 1. Compared with the composite device made by nanowire shielding, this method can prepare complex composite devices. Different composite devices can be made by simply changing the exposure pattern and fine-tuning it. Different types and thicknesses of metal films can be obtained by replacing different coating sources, and the interface properties can be flexibly changed by etching.
[0076] 2. Compared with the smart wall process for making high-quality devices, this process has good process conditions and can be easily transferred to other similar types of devices. The production is relatively simple and more complex devices can be made.
[0077] 3. The universal high-quality composite device micro-nano processing method provided by the present invention can change the interface properties by controlling the etching time. The process adopts a universal micro-nano processing method, including an electron beam exposure system, a plasma etching system and a coating system. The high precision of electron beam exposure can be used to process small structures and perform precise overlay, and complex devices can be manufactured. The plasma etching system can remove the adsorbed gas and oxide layer on the surface of the semiconductor material, and the interface properties can be changed. The coating system is used to deposit metal films, wherein the coating system can be an electron beam evaporation coating or a magnetron sputtering system, and different metal materials and films of different thicknesses can be deposited. A cold bottom plate can also be used to further improve the film quality. We have made different types of devices and deposited films of different metals and different thicknesses. A particularly thin film was also deposited using a cold bottom plate. The morphology shows that a clean device has been made, and the transmission electron microscope image shows that the film material grows epitaxially on the surface of the semiconductor nanowire. The transport data observes a quantized conductivity platform, and a very high transmission coefficient is obtained by data fitting. These all show high-quality devices. We also observed an increase in carrier concentration caused by the interface band bending caused by etching. The above shows that this process is suitable for different types of devices, can deposit different materials, and form films of different thicknesses. The interface properties can also be changed by etching. This provides a solid foundation for the future production and research of composite devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0079] Figure 1 A scanning electron microscope image of a composite device of nanowires and thick aluminum prepared in Example 1 of the present invention is shown.
[0080] Figure 2 A scanning electron microscope image of a composite device of nanowires and thin lead prepared in Example 2 of the present invention is shown.
[0081] Figure 3 A transmission electron microscope image of the interface of the composite device of nanowires and thick aluminum prepared in Example 1 of the present invention is shown.
[0082] Figure 4 The transport data and fitting result diagram of the composite device of nanowires and thick aluminum in Example 3 of the present invention are shown; wherein, Figure 4(b), 4(c), and 4(d) show the changes in the conductance of the device with interface etching for 20s, 40s, and 2min as the bias voltage Vbias and back gate voltage (Vbg) change, respectively. It can be seen that aluminum induces a superconducting energy gap of about 0.2meV in the nanowire. Figure 4 (a) The figure above shows the transverse cross-sections of the three devices outside the superconducting energy gap, that is, the change of conductance with the back gate. On the one hand, the quantized conductance platform can be seen in the three curves, reflecting the nature of ballistic transport in the conductive channel. On the other hand, by fitting the curves of conductance changing with bias voltage under different back gates, the corresponding number of conductive channels and the transmission coefficient of the corresponding channel can be obtained. Figure 4 (a) The illustration in the figure above is an example, the circular marks are data, and the triangle marks are fitting curves. The corresponding results of the three devices are shown in Figure 4 (a) As shown in the following three figures, it can be seen that as the back gate voltage increases, the number of conductive channels gradually increases and decreases, and the transmission coefficient of the conductive channel quickly increases to 1, which also reflects the high quality of the device. On the other hand, at the same back gate voltage, as the device etching time increases, the conductivity increases. This is because etching causes the energy band to bend at the interface. The longer the etching time, the more severe the energy band bending, the more electrons accumulate, and the greater the conductivity. The charge accumulation at the interface is conducive to the occurrence of the superconducting proximity effect, which is the effect of etching on the interface.
[0083] Figure 5 A flow chart of the method for preparing and modifying the interface of the semiconductor composite device of the present invention is shown. DETAILED DESCRIPTION
[0084] The present invention is further described below by means of specific examples. However, it should be understood that these examples are only used for more detailed and specific description and should not be understood as limiting the present invention in any form.
[0085] This section generally describes the materials and test methods used in the experiments of the present invention. Although many materials and operating methods used to achieve the purpose of the present invention are well known in the art, the present invention is still described as detailed as possible. It is clear to those skilled in the art that in the context, if not specifically stated, the materials and operating methods used in the present invention are well known in the art.
[0086] The reagents and instruments used in the following examples are as follows:
[0087] Reagents:
[0088] PMMA, purchased from MicroChem;
[0089] Acetone and isopropanol were purchased from Beijing Tongguang Fine Chemical Company;
[0090] The developer, a mixed solution of methyl isobutyl ketone (MIBK) and isopropyl alcohol (IPA) in a ratio of 1:3, was purchased from Kayaku Advanced Materials Co., Ltd.
[0091] instrument:
[0092] Thermal field emission scanning electron microscope, purchased from Raith GmbH, model 5-OR100-EOC.
[0093] The ultra-high vacuum electron beam multi-cavity evaporation coating system was purchased from PLASSYS BESTEK SAS, model MEB550SL3.
[0094] The radio frequency magnetron sputtering coating machine was purchased from Beijing Oriental Gaide Vacuum Technology Co., Ltd., model JSD500.
[0095] Example 1
[0096] This embodiment is used to illustrate the preparation and interface modification method of the semiconductor composite device of the present invention.
[0097] This embodiment takes semiconductor nanowires and thick aluminum as an example, and the specific preparation steps are as follows:
[0098] Step 1, spin coating photoresist. Spin coating the substrate substrate with nanowires with suitable photoresist. The selection of photoresist depends on the required thickness, precision, etc., and the substrate is baked and vitrified. If necessary, a vacuum pump can be used to remove the solvent. The selection of photoresist is based on the nanowire material. We use positive photoresist here. According to the required precision, we use polymethyl methacrylate (PMMA). According to the structural requirements, etching time, metal film thickness, etc., photoresists of different concentrations can be used. After spin coating, photoresists of different thicknesses are obtained. And the required exposure voltage and dosage as well as graphic design are explored to meet the experimental requirements. The substrate used in this embodiment is a 300nm SiO2 thick silicon wafer (length and width are 5mm), the photoresist is polymethyl methacrylate (PMMA), the baking temperature is 180°C, and the baking time is 3 minutes.
[0099] Step 2: Electron beam exposure and development. Design the exposure pattern according to the required composite device, select the appropriate acceleration voltage and dose, and expose the pattern. After exposure, use the corresponding developer to develop the exposed photoresist. The acceleration voltage used in this embodiment is 20kV and the dose is 260μC / cm 2The developer is a mixed solution of methyl isobutyl ketone (MIBK) and isopropanol (IPA) in a volume ratio of 1 to 3, the developing time is 3 minutes, the fixing solution is isopropanol, and the fixing time is 1 minute.
[0100] Step three, etching and coating. Etching has multiple parameter selections, such as gas, air pressure, power, acceleration voltage, etc. After changing the conditions, the subsequent composite device morphology and measurement results are used to optimize the parameters and summarize the impact of etching on the interface. After the sample is placed in the etching chamber and evacuated, select the appropriate etching gas, air pressure, plasma power and acceleration voltage to etch the nanowire contact interface. And explore the impact of etching on the oxide layer and the interface. After the etching is completed, the sample is transferred to the coating chamber under vacuum to evaporate the metal film. When other coating systems are selected, after the etching is completed, it is quickly transferred to other coating systems to evaporate the metal film. If necessary, it can be transferred to the coating chamber in the etching system to evaporate a small amount of Ti metal to prevent direct oxidation of the semiconductor nanowires and affect the interface. The etching gas used in this embodiment is argon, the air pressure is 0.03Pa, the ion beam current is 10mA and the ion beam voltage is 260V, and the etching time is 40 seconds. After the etching is completed in this embodiment, the sample is transferred to the coating chamber under vacuum to evaporate a thick aluminum metal film.
[0101] Step 4: Degumming. Place the coated substrate into a degumming solution, such as acetone, to remove excess film and form a composite device. For more complex devices, other materials and combined devices can be evaporated by repeating the above steps. The degumming solution used in this embodiment is acetone.
[0102] The determination of this process method requires exploring and determining the parameters of each step based on actual conditions, such as substrate material, electrode thickness, oxide layer thickness, etc., and then promoting the device type and thin film material.
[0103] Figure 1 This is a scanning electron microscope image of a composite device of nanowires and thick aluminum made using this method. After etching, the sample is directly transferred to the coating vacuum chamber to evaporate the metal film.
[0104] Figure 3 The transmission electron microscope image of the interface of the composite device of nanowire and thick aluminum prepared in Example 1 of the present invention is shown. We can see that the aluminum is a single crystal and grows epitaxially at the interface, which reflects the high quality of the device made by this process.
[0105] Example 2
[0106] This embodiment is used to illustrate the preparation and interface modification method of the semiconductor composite device of the present invention.
[0107] This embodiment takes semiconductor nanowires and thin lead as examples, and the specific preparation steps are as follows:
[0108] Step 1, spin coating photoresist. The substrate substrate carrying the nanowire is spin coated with a suitable photoresist. The selection of the photoresist is based on the required thickness, precision, etc., and the photoresist is baked and vitrified. If necessary, a vacuum pump can be used to evacuate and remove the solvent. The selection of the photoresist is based on the nanowire material. We use positive photoresist here. According to the required precision, we use polymethyl methacrylate (PMMA). According to the structural requirements, etching time, metal film thickness, etc., photoresists of different concentrations can be used. After spin coating, photoresists of different thicknesses are obtained. And explore the required exposure voltage and dosage and graphic design, etc., to meet the experimental requirements. The substrate used in the present embodiment is a 300nm SiO2 thick silicon wafer (length and width are 5mm), and the photoresist is polymethyl methacrylate (PMMA).
[0109] Step 2: Electron beam exposure and development. Design the exposure pattern according to the required composite device, select the appropriate acceleration voltage and dose, and expose the pattern. After exposure, use the corresponding developer to develop the exposed photoresist. The acceleration voltage used in this embodiment is 20kV and the dose is 260μC / cm 2 The developer is a mixed solution of methyl isobutyl ketone (MIBK) and isopropanol (IPA) in a ratio of 1 to 3, the developing time is 3 minutes, the fixing solution is isopropanol, and the fixing time is 1 minute.
[0110] Step three, etching and coating. There are multiple parameter options for etching, such as gas, air pressure, power, acceleration voltage, etc. After changing the conditions, the subsequent composite device morphology and measurement results are used to optimize the parameters and summarize the impact of etching on the interface. After the sample is placed in the etching chamber and evacuated, select the appropriate etching gas, air pressure, plasma power and acceleration voltage to etch the nanowire contact interface. And explore the impact of etching on the oxide layer and the interface. After the etching is completed, the sample is transferred to the coating chamber in a vacuum environment to evaporate the metal film. When other coating systems are selected, after the etching is completed, it is quickly transferred to other coating systems to evaporate the metal film. If necessary, it can be transferred to the coating chamber in the etching system to evaporate a small amount of Ti metal to prevent direct oxidation of the semiconductor nanowires and affect the interface. The etching gas used in this embodiment is argon, the air pressure is 0.03Pa, the ion beam current is 10mA and the ion beam voltage is 260V, and the etching time is 4 minutes. After the sample of this embodiment is etched, it is transferred to the coating chamber in the etching system to evaporate a small amount of titanium metal to prevent direct oxidation of the semiconductor nanowires and affect the interface, and then quickly transferred to magnetron sputtering to deposit a thin lead metal film using a cold bottom plate. It can be seen that the device morphology is very good, and the junction spacing is very small. The two devices prepared in Examples 1 and 2 belong to different types of devices, and different metals are evaporated with large differences in thickness, which reflects the versatility of the process method.
[0111] Step 4: Degumming. Place the coated substrate into a degumming solution, such as acetone, to remove excess film and form a composite device. For more complex devices, other materials and combined devices can be evaporated by repeating the above steps. The degumming solution used in this embodiment is acetone.
[0112] The determination of this process method requires exploring and determining the parameters of each step based on actual conditions, such as substrate material, electrode thickness, oxide layer thickness, etc., and then promoting the device type and thin film material.
[0113] Figure 2 This is a composite device of nanowires and thin lead fabricated using this method. After the sample is etched, it is quickly transferred to magnetron sputtering, where a thin lead metal film is evaporated using a cold bottom plate. It can be seen that the device morphology is very good, the junction spacing is very small, and the two devices are of different types, with different metals evaporated and the thickness difference is large, which reflects the versatility of this process method.
[0114] Example 3
[0115] This example is used to illustrate the transport data and fitting results of the composite device of nanowires and thick aluminum prepared in Example 1 of the present invention.
[0116] (1) The composite device of nanowires and thick aluminum with different etching times is placed in a low-temperature thermostat and lowered to the lowest temperature of about 10 mK.
[0117] (2) The two-dimensional graph data of differential conductance changing with bias voltage and back gate voltage is measured using AC phase-locked technology.
[0118] (3) The short junction scattering model is used to fit the curve of differential conductance changing with bias voltage to obtain the corresponding number of conductive channels and the transmission coefficient of the corresponding channel.
[0119] Figure 4 The transport data and fitting result diagram of the composite device of nanowires and thick aluminum in Example 3 of the present invention are shown; wherein, Figure 4 (b), 4(c), and 4(d) show the changes in the conductance of the device with interface etching for 20s, 40s, and 2min as the bias voltage Vbias and back gate change, respectively. It can be seen that aluminum induces a superconducting energy gap of about 0.2meV in the nanowire. Figure 4 (a) The figure above shows the transverse cross-sections of the three devices outside the superconducting energy gap, that is, the change of conductance with the back gate. On the one hand, the quantized conductance platform can be seen in the three curves, reflecting the nature of ballistic transport in the conductive channel. On the other hand, by fitting the curves of conductance changing with bias voltage under different back gates, the corresponding number of conductive channels and the transmission coefficient of the corresponding channel can be obtained. Figure 4 (a) The illustration in the figure above is an example, the circular marks are data, and the triangles are fitting curves. The corresponding results of the three devices are shown in Figure 4 (a) As shown in the following three figures, it can be seen that as the back gate voltage increases, the number of conductive channels gradually increases and decreases, and the transmission coefficient of the conductive channel quickly increases to 1, which also reflects the high quality of the device. On the other hand, at the same back gate voltage, as the device etching time increases, the conductivity increases. This is because etching causes the energy band to bend at the interface. The longer the etching time, the more severe the energy band bending, the more electrons accumulate, and the greater the conductivity. The charge accumulation at the interface is conducive to the occurrence of the superconducting proximity effect, which is the effect of etching on the interface.
[0120] The above shows that this process can be used to make different types of devices, use metal materials of different types and thicknesses, and change the interface properties by changing the etching time.
[0121] As research progresses, different properties need to be studied in the same material, requiring different device types, different materials and interface property changes. This universal approach and treatment of interfaces will undoubtedly make research more convenient.
[0122] Although the present invention has been described to a certain extent, it is obvious that appropriate changes in various conditions can be made without departing from the spirit and scope of the present invention. It is understood that the present invention is not limited to the embodiments described, but belongs to the scope of the claims, which includes equivalent replacements of each factor described.
Claims
1. A method for preparing a semiconductor composite device, characterized in that: The preparation method prepares a semiconductor composite device by a micro-nano processing method, and performs interface modification by controlling the micro-nano processing steps; wherein, The micro-nano processing method is selected from one or more of the following: electron beam exposure, plasma etching, and thin film deposition; Preferably, the thin film deposition method is selected from one or more of the following: electron beam evaporation, magnetron sputtering, and resistance thermal evaporation.
2. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Design exposure patterns for semiconductor composite devices; (2) exposing and developing based on step (1); (3) etching the interface of the semiconductor material based on step (2); (4) depositing a thin film based on step (3); (5) removing the glue and peeling off the excess film to obtain the semiconductor composite device; Preferably, the interface modification is performed by controlling the etching conditions in step (3).
3. The preparation method according to claim 1 or 2, characterized in that: In the step (1), before designing the exposure pattern of the semiconductor material, the step further includes: spin coating a photoresist on a substrate carrying the semiconductor material and baking the photoresist; Preferably, the baking time is 1 to 15 minutes, more preferably 1 to 5 minutes, and further preferably 1 to 3 minutes; Preferably, the photoresist is selected from one or more of the following: PMMA, ZEP, EBR-9, HSQ, PBS, COP, more preferably selected from one or more of the following: PMMA, ZEP, EBR-9, PBS, further preferably: PMMA or ZEP; and / or Preferably, the substrate is selected from one or more of the following: SiO2, Si3N4, intrinsic silicon, sapphire, GaN, mica sheet, quartz glass, more preferably selected from one or more of the following: SiO2, Si3N4, intrinsic silicon, sapphire, GaN, further preferably selected from one or more of the following: SiO2, intrinsic silicon, sapphire.
4. The preparation method according to any one of claims 1 to 3, characterized in that In the step (2), the pattern designed in the step (1) is exposed and developed by an electron beam exposure system; Preferably, the composite device structure is defined by the electron beam exposure system, and its structure width and position accuracy are both less than 100 nm, more preferably less than 90 nm, further preferably less than 70 nm, and further preferably less than 50 nm; Preferably, the developer is selected from one or more of the following: MIBK:IPA mixed solution, xylene:p-dioxane mixed solution, MIAK:2-pentanone mixed solution, MEK:ethanol mixed solution, TMAH:DI mixed solution, more preferably selected from one or more of the following: MIBK / IPA mixed solution, xylene / p-dioxane mixed solution, MIAK / 2-pentanone mixed solution, further preferably: MIBK:IPA mixed solution or xylene:p-dioxane mixed solution; Preferably, the development time is 30 to 600 s, more preferably 30 to 300 s, and further preferably 30 to 180 s; and / or Preferably, the exposure time is 1 to 300 s, more preferably 1 to 180 s, and further preferably 1 to 60 s.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step (3), the adsorbed atoms and the oxide layer on the surface of the semiconductor material are removed by a plasma etching system, and the interface properties are changed.
6. The preparation method according to claim 5, characterized in that: In the step (3), The etching time is 5 to 600 s, preferably 5 to 240 s, more preferably 5 to 120 s; The etching gas is selected from one or more of the following: Ar, O2, CF4, SF6, NF3, SiCl4, CH4, H2, preferably selected from one or more of the following: Ar, O2, CF4, SF6, NF3, SiCl4, more preferably selected from one or more of the following: Ar, O2, CF4, SF6; The etching gas pressure is ≤10Pa, preferably ≤8Pa, more preferably ≤5Pa; The etching ion beam current is ≥10mA, preferably ≥15mA, more preferably ≥20mA; and / or The etching ion beam voltage is ≤1000V, preferably ≤800V, and more preferably ≤600V.
7. The preparation method according to any one of claims 1 to 6, characterized in that In the step (4), the film is transferred to the film deposition chamber by vacuum to avoid exposure to the atmosphere, which may cause surface adsorption or secondary oxidation of the interface; wherein the film is a metal film; Preferably, the material of the film is selected from one or more of the following: aluminum, lead, niobium titanium nitride, tin, more preferably selected from one or more of the following: aluminum, lead, niobium titanium nitride, further preferably aluminum or lead; and / or Preferably, the step (4) further comprises using a cold base plate to improve the quality of the deposited film.
8. The preparation method according to any one of claims 1 to 6, characterized in that In the step (4), a transition layer is deposited to prevent direct oxidation of the interface, and then the film is transferred to a thin film deposition device for thin film deposition; wherein the thin film is a metal thin film; Preferably, the material of the film is selected from one or more of the following: aluminum, lead, niobium titanium nitride, tin, more preferably selected from one or more of the following: aluminum, lead, niobium titanium nitride, further preferably aluminum or lead; and / or Preferably, the step (4) further comprises using a cold base plate to improve the quality of the deposited film.
9. The preparation method according to any one of claims 1 to 8, characterized in that: In the step (5), the sample after the thin film deposition is placed in a degumming solution, and the excess thin film is peeled off to obtain the semiconductor composite device; Preferably, the degumming solution is selected from one or more of the following: acetone, methyl isobutyl ketone, butyl acetate, dimethylformamide, dichloromethane, propylene glycol monomethyl ether acetate, trichloroethylene, N-methylpyrrolidone, methyl ethyl ketone, more preferably selected from one or more of the following: acetone, methyl isopropyl ketone, butyl acetate, dimethylformamide, propylene glycol monomethyl ether acetate, trichloroethylene, further preferably selected from one or more of the following: acetone, methyl isopropyl ketone, butyl acetate, dimethylformamide, propylene glycol monomethyl ether acetate; and / or Preferably, the auxiliary method for degumming is selected from one or more of the following: blowing with a dropper, blowing with an air gun, and ultrasonic vibration.
10. A semiconductor superconducting composite device, characterized in that: The semiconductor superconducting composite device is manufactured according to the manufacturing method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electro plating method for shallow-junction and dense-grating micron electrode
CN105845751A
Insulating layer windowing process implemented on DFB laser ridge waveguide through nano-imprint method
CN108963753A
Multistage micro-nano structure and preparation method and application thereof
CN115520833A
Preparation method for hot electron transistor in high frequency gallium nitride / graphene heterojunction
WO2019153431A1
Preparation method for silicon nanometer needle array having extra-high depth to width ratio
WO2021083080A1
